Implementation of IPAS with an Inquiry Learning Model in Grade 4 Primary School - Wulandari, Aulia; Sukarno, Sukarno; Matsuri, Matsuri (Universitas Pendidikan Indonesia, 2023)
IPAS (Ilmu Pengetahuan Alam dan Sosial/Natural and Social Sciences) constitutes essential subjects in the implementation of the Merdeka Curriculum in primary schools. The primary goal of integrating IPAS is to enable students to effectively manage their natural and social environment as a whole. In light of this objective, the researcher recognized the necessity of conducting this research. The research employs a qualitative approach with a case study method conducted at one of the elementary schools in Sukoharjo District, Central Java. The respondents in this research include the school principal, fourth-grade teachers, first-grade teachers, and fourth-grade students. Data collection was carried out through interviews, observation, and documentation, followed by technical triangulation to validate the field findings. Based on the results obtained from the implementation of IPAS learning using the inquiry learning model, it is established that natural and social sciences were taught separately in the first and second semesters. The results of research conducted in the second semester reveal that IPAS learning activities on social science material have been implemented effectively in terms of planning, execution, and evaluation, with a focus on adhering to the syntax of the inquiry learning model. Obstacles to IPAS learning include educators’ lack of readiness for curriculum changes, limited training and information regarding the curriculum, a lack of skill in using technology, and classroom conditions that are not conducive. Efforts made include increasing the competence of educators through teacher working group forums, participating in training, and managing classes to ensure conducive learning activities. This research is expected to serve as a valuable reference for studying the implementation of IPAS with the inquiry learning model in the Merdeka Curriculum.